Serial evaluation of sequential organ failure assessment score in predicting 1-year mortality in critically Ill patients - Md Ralib, Azrina; Mohd Said, Nor Azura; Ramly, Nur Fariza; Nanyan, Suhaila; Ismail, Mohd Nizamuddin; Mat Nor, Mohd Basri (Kulliyyah of Medicine, International Islamic University Malaysia, 2022)
Introduction: The prediction of long-term prognosis or outcome of critically ill patients in the intensive care unit (ICU) is important for prognostication and administration purposes. The Sequential Organ Failure Assessment (SOFA) score was developed in order to estimate organ failure in patients with sepsis. Organ failures have been associated with mortality and hence SOFA score has been validated as an outcome measure. To the best of our knowledge, the association of SOFA, and serial SOFA score with 1-year mortality has not been well established. Materials and method: This was a retrospective observational cross sectional study using the existing record of patients admitted to the general ICU at the Sultan Ahmad Shah Medical Centre from the 1st June 2017 to the 30th May 2018. Data was collected from daily clinical charts and medical records of patients. SOFA score on day-1, day-3, day-3, and on discharge were recorded and subsequently delta SOFA was calculated. Results: Data from a total of 120 patients were collected. SOFA score within 3 days of admission predicted 1-year mortality, with the highest prediction for on SOFA score on discharge from ICU. Serial SOFA score measured within 24 hours (day-1 to day-2) and 48 hours (day-1 to day-3) did not predict mortality; however, delta SOFA involving SOFA on discharge did. Cardiovascular and renal scores were the most significant individual component of SOFA score that contributed to 1-year mortality. Conclusion: SOFA score measured on discharge from ICU plays a key important factor in contributing for the prediction of 1-year mortality. Cardiovascular and renal scores were the most significant component that warrant risk stratification measures using the parameters.